Training Success Factors in The Coast Guard Special Operations Course - Cadalso, Ramil R. (Future Science / FSH-PH Publications, 2025)
The Coast Guard Special Operations Course has experienced a 33% dropout rates covering training program from 2018 to 2024, highlighting the need to identify the underlying factors contributing to trainee success or failure. This mixed-methods study utilized a concurrent triangulation design to examine these factors comprehensively. Quantitative data were collected from 243 respondents who successfully completed the CGSOC training from 2018 until August 2024. The analysis, conducted using Exploratory Factor Analysis, revealed five key dimensions influencing training success: (1) Career Advancement and Personal Motivation, (2) Training Environment and Support, (3) Training Facility and Resource Adequacy, (4) Family Support and Guidance, and (5) Family Concerns and Peer Support. Concurrently, qualitative data were gathered through in-depth interviews with five participants who did not complete the training, which provided additional context and in-depth understanding of the challenges trainees face. The study found that trainees’ intrinsic motivation, a supportive training environment, and robust family and peer support are crucial for their success. On the other hand, challenges such as homesickness, financial difficulties, and inadequate preparation were identified as major obstacles that contribute to attrition. These findings emphasize the need for targeted interventions to optimize training retention and outcomes. The results suggest that fostering mentorship and peer support systems could mitigate the negative impacts of these challenges, thereby improving completion rates. Future research may explore the role of structured peer mentorship and family engagement strategies in high-stress law enforcement training environments.